Active Moderate-to-Severe Graves' Orbitopathy in a Patient With Type 2 Diabetes Mellitus and Vascular Complications - Urselli, Francesca; Pontieri, Gilda; Peschi, Livia; Liccardi, Alessia; Ruggiero, Anna Rita; Biondi, Bernadette (Frontiers in Endocrinology, 2019)
BACKGROUND: Graves’ orbitopathy (GO) is the main extrathyroidal manifestation of Graves’ disease (GD). Diabetes mellitus (DM) has been reported to be a risk factor in patients with GO. Moreover, GO can be more frequent and severe in type 2 diabetes patients. High doses of intravenous glucocorticoids represent the first line treatment of moderate-to-severe and active GO according to the international guidelines. However, this therapy is contraindicated in uncontrolled diabetes and in patients with increased cardiovascular risk. Some antidiabetic drugs can exacerbate GO. We reported the clinical case of an active and moderate-to-severe GO in a patient with uncontrolled type 2 DM and vascular complications. CASE REPORT: A 61-year-old patient came to our ambulatory for a recurrence of GD and a moderate-to-severe bilateral GO. The patient had uncontrolled type 2 DM during insulin therapy and a history of micro- and macrovascular complications. At the physical examination the clinical activity score was 5 and the severity of GO was moderate-to-severe. A blood sample showed overt hyperthyroidism and the persistence of anti-TSH receptor antibodies (TRAb) during treatment with methimazole. A computed tomography scan showed a moderate-to-severe bilateral exophthalmos. We discuss the benefit/risk of treatment of GO in our patient. CONCLUSION: The available guidelines do not focus on the treatment of diabetic patients with uncontrolled diabetes and severe vascular complications, therefore our patient represents a difficult therapeutic challenge. The screening of thyroid function and the evaluation of GO could be useful in diabetic patients with autoimmune thyroid disease to perform a correct treatment of these disorders.